INTERPRETASI AYAT-AYAT TEOLOGI FEMINIS PERSPEKTIF MUHAMMAD SYAHRUR (FIQH AL-MAR’AH SEBAGAI TEOLOGI FEMINIS MELAWAN ORTODOKSI ISLAM DALAM ISU PEREMPUAN) - Syamsul Wathani; Beko Hendro (CV. Doki Course and Training, 2023)
There are several questions raised in this article, what is Syahrur's basic view of Islamic theology on women? How did the emergence and discussion of women's issues in the book Nahwa Ushul al-Jadidah What is fiqh al-Mar'ah? and how is the connection between the birth of the book in contemporary Islamic discourse and the Islamic State? The main data sources for the inner articles are two books by Syahrur, al-Islam wa al-Īmān: Manzhūmah al-Qiyam and Nahwa Ushul al-Jadidah Li Fiqh al-Mar'ah. The position of the research article in taking the space of discursive study, the discourse of the emergence of works with the domination of power in the Islamic State after the fall of Turkey. By analyzing the contents of the book (content analysis) and reading the discourse or historical data and the context of the birth of the book and the author's agent in the book, this article finds several main conclusions in the state's political discourse, Syahrur's feminist theological ideas and ideas in his work were born as an effort to fight against the hegemony of Islamic rule in Syria. Syahrur's thoughts can be placed as a tool or as a method in formulating Islam as a social theology, Islam that is not far from the reality of the existence of its people